2014
DOI: 10.1177/0145445514531016
|View full text |Cite
|
Sign up to set email alerts
|

Variables Associated With Tic Exacerbation in Children With Chronic Tic Disorders

Abstract: Research has shown that motor and vocal tics fluctuate in frequency, intensity, and form in response to environmental and contextual cues. Behavioral models have proposed that some of the variation in tics may reflect context-dependent interactive learning processes such that once tics are performed, they are influenced by environmental contingencies. The current study describes the results of a function-based assessment of tics (FBAT) from a recently completed study comparing Comprehensive Behavioral Interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 32 publications
2
46
0
1
Order By: Relevance
“…Consistent with previous research (Carr et al, 1996; Himle et al, in press; Scotti et al, 1994; Watson & Sterling, 1998), this study found that the vast majority of youth with CTDs report experiencing consequences for ticcing (cf. Himle et al, in press), and that these consequences (as measured by TARS scores) are positively correlated with tic severity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous research (Carr et al, 1996; Himle et al, in press; Scotti et al, 1994; Watson & Sterling, 1998), this study found that the vast majority of youth with CTDs report experiencing consequences for ticcing (cf. Himle et al, in press), and that these consequences (as measured by TARS scores) are positively correlated with tic severity.…”
Section: Discussionsupporting
confidence: 91%
“…Only one study has evaluated perceived associations between tic exacerbation and environmental consequences among individuals with CTDs. Himle and colleagues (in press) analyzed data from clinical interviews with 51 youth receiving behavior therapy for CTDs and their parents. Children and their parents were asked about a number of social consequences that may occur during periods of tic exacerbation, and the clinician dichotomously recorded whether or not each consequence had been endorsed.…”
mentioning
confidence: 99%
“…Although the etiology of TS is primarily biologically determined, there is considerable evidence to suggest that behavioral antecedents and consequences may influence tic expression/suppression [15,16]. Additionally, emerging data suggests that expression of tic symptoms can also result in environmental consequences [17].…”
mentioning
confidence: 99%
“…Finally, it's worth noting that while the function-based elements of CBIT might not have been particularly relevant for Hiro, results from the child CBIT randomized controlled trial found that out of 51 children randomized to CBIT, all participants endorsed at least two ticexacerbating antecedents and all but two endorsed at least one tic-exacerbating consequence (Himle et al, 2014). These findings strongly suggest that not taking the time to conduct a thorough functional assessment could, more times than not, result in the therapist missing out on important treatment-related information.…”
Section: The Role Of Theory: Becoming a Culinarianmentioning
confidence: 99%